The Use of Whispering Game as Intervention to Enhance Students’ Topographic Memory: A Qualitative Action Research - Arcite, John Patrick; Tomales, Myra Fe; Ancla, Tedd Joshua (MO.RI Publishing, 2024)
Topographic memory plays a vital role in learning, significantly impacting learning efficiency however researchers recognized poor memory skills as a common hurdle for students in their academic pursuits. To tackle this issue, the researchers focused on employing the Whispering Game to enhance the topographic memory skills of fifteen (15) grade 8 students. Through in-depth interviews and focus group discussions, the researchers collected data on the students' memory skills in relation to the Topography of the Continents. After six weeks of implementing the intervention, data analysis revealed several themes. It became evident that the students possessed varying degrees of memory skills, ranging from decent to null. Moreover, the study shed light on the challenges that faced by the students in their learning, such as lack of concentration, information overload, unfamiliarity with certain concepts, and gaps in discussions. These factors directly influence students' behavior and interest in learning. However, the introduction of the Whispering Game proved beneficial. Students reported that the game facilitated knowledge acquisition and improved their memory skills by offering opportunities for practice and employing memory-enhancing tactics. Additionally, students recognized the importance of continuous learning, emphasized the need for concentration to retain information effectively, and enjoyed the learning experience. Overall, the utilization of the Whispering Game as a means to enhance topographic memory skills not only enables students to improve their present learning abilities but also equips them with valuable skills for future endeavors.